Changes in Semsc, Glucosinolates and Sulforaphane Levels, and in Proteome Profile in Broccoli (Brassica Oleracea Var. Italica) Fertilized with Sodium Selenate - Moenne-Munoz, A; Mahn-Osses, A; Barrientos-Carvacho, H; Barrientos-Carvacho, H (2013)
The aim of this work was to analyze the effect of sodium selenate fortification on the content of selenomethyl selenocysteine (SeMSC), total glucosinolates and sulforaphane, as well as the changes in protein profile of the inflorescences of broccoli (Brassica oleracea var. Italica). Two experimental groups were considered: plants treated with 100 ?mol/L sodium selenate (final concentration in the pot) and control plants treated with water. Fortification began 2 weeks after transplantation and was repeated once a week during 10 weeks. Broccoli florets were harvested when they reached appropriate size. SeMSC content in broccoli florets increased significantly with sodium selenate fortification; but total glucosinolates and sulforaphane content as well as myrosinase activity were not affected. The protein profile of broccoli florets changed due to fortification with sodium selenate. Some proteins involved in general stress-responses were up-regulated, whereas down-regulated proteins were identified as proteins involved in protection against pathogens. This is the first attempt to evaluate the physiological effect of fortification with sodium selenate on broccoli at protein level. The results of this work will contribute to better understanding the metabolic processes related with selenium uptake and accumulation in broccoli. © 1996-2013 MDPI AG (Basel, Switzerland).